Virtual learning objects for the development of english vocabulary in students of tenth grade of Velasco Ibarra Educational Unit, Guamote canton, period 2023 – 2024. - Castro Molina, Yadira Patricia (2024)
Education, in all fields and domains, has undergone many changes over the years. In the case of English, in connection with the technology boom, there have been attempts to change traditional teaching and learning methods by adapting new digital resources, such as virtual learning objects (VLOs), to develop various language skills, especially vocabulary. This research report aims to determine that the use of virtual learning objects helps to develop English vocabulary. The study was conducted with 10th grade students of the E.G.B. of the “Velasco Ibarra” educational unit. Based on these statements, a quasi-experimental design with a quantitative approach was chosen, with an applied type based on objective, a field type based on geographical location, and a cross-sectional type based on the time. As a result of this study, data were collected from a purposive non-probability sample of 56 students, divided into two groups, the first being a control group of 27 students (parallel A) and the second being an experimental group (parallel B) of 29 students, a test technique and a questionnaire instrument were used. The results showed that the use of the VLOs significantly improves the English vocabulary; the use of tools such as genially, prezzi, workwall, paddle, liveworksheet, etc., not only improves this skill, but also greater interaction, engagement, and most importantly, it stirred interest and motivation to learn this language.